Penerapan Kincir Air Otomatis Berbasis Sensor Suhu untuk Meningkatkan Efisiensi Budidaya Ikan Nila di Kelompok Kegiatan Wildatul Sholihah, Bogor - Basri, Hasan; Arie Aryanto; Ihsan Alparisi; Fajar Mahardika (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2025)
This community service activity aims to improve the efficiency of tilapia pond management through the implementation of a manually operated waterwheel system for the Wildatul Sholihah Activity Group in Bojong Village, Bogor Regency. The partner’s challenges include fluctuating water temperatures, low oxygen levels, and limited manpower, as pond maintenance is only carried out on weekends. As an initial solution, the service team conducted training and installed a simple manually operated waterwheel unit. The activity took place on May 28, 2025, and involved several stages: coordination, module preparation, equipment assembly, technical training, and field testing. The results showed that the waterwheel successfully improved water circulation and temperature stability, while also reducing the frequency of manual water replacement. Training participants demonstrated increased technical understanding, high enthusiasm, and the ability to operate and maintain the device independently. This initiative had a tangible impact in supporting more efficient and sustainable tilapia farming. In the future, the system has the potential to be further developed with the integration of digital technologies such as IoT-based monitoring systems